Synthesis of Disulfide Surrogate Peptides Incorporating Large‐Span Surrogate Bridges Through a Native‐Chemical‐Ligation‐Assisted Diaminodiacid Strategy. (17th March 2020) - Qu, Qian; Gao, Shuai; Wu, Fangming; Zhang, Meng‐Ge; Li, Ying; Zhang, Long‐Hua; Bierer, Donald; Tian, Chang‐Lin; Zheng, Ji‐Shen; Liu, Lei
Abstract: The use of synthetic bridges as surrogates for disulfide bonds has emerged as a practical strategy to obviate the poor stability of some disulfide‐containing peptides. However, peptides incorporating large‐span synthetic bridges are still beyond the reach of existing methods. Herein, we report a native chemical ligation (NCL)‐assisted diaminodiacid (DADA) strategy that enables the robust generation of disulfide surrogate peptides incorporating surrogate bridges up to 50 amino acids in length. This strategy provides access to some highly desirable but otherwise impossible‐to‐obtain disulfide surrogates of bioactive peptide. The bioactivities and structures of the synthetic disulfide surrogates were verified by voltage clamp assays, NMR, and X‐ray crystallography; and stability studies established that the disulfide replacements effectively overcame the problems of disulfide reduction and scrambling that often plague these pharmacologically important peptides. Abstract : Alternative Brücke : Eine durch native chemische Ligation gestützte Diaminodisäuren‐Strategie wurde für die chemische Synthese von Peptid‐Disulfid‐Ersätzen entwickelt, wobei Ringgrößen von bis zu 50 Aminosäuren gebildet wurden. Die Methode ermöglicht das Engineering von biologisch interessanten Disulfid‐enthaltenden Peptiden und erweitert den Horizont von Peptid‐basierten Forschungswerkzeugen sowie diagnostischen bzw. therapeutischen Reagenzien.